Interfacing Machine Learning and Microbial Omics: A Promising Means to Address Environmental Challenges - McElhinney, James M. W. R.; Catacutan, Mary Krystelle; Mawart, Aurelie; Hasan, Ayesha; Dias, Jorge (Frontiers in Microbiology, 2022)
Microbial communities are ubiquitous and carry an exceptionally broad metabolic capability. Upon environmental perturbation, microbes are also amongst the first natural responsive elements with perturbation-specific cues and markers. These communities are thereby uniquely positioned to inform on the status of environmental conditions. The advent of microbial OMICs has led to an unprecedented volume of complex microbiological datasets. Importantly, these datasets are rich in biological information with potential for predictive environmental classification and forecasting. However, the patterns in this information are often hidden amongst the inherent complexity of the data. There has been a continued rise in the development and adoption of machine and deep learning (ML and DL) architectures for solving research challenges of this sort. Indeed, the interface between molecular microbial ecology and AI appears to show considerable potential for significantly advancing environmental monitoring and management practices through their application. Here, we provide a primer for ML, highlight the notion of retaining biological sample information for supervised ML, discuss workflow considerations and review the state of the art of the exciting, yet nascent, interdisciplinary field of ML-driven microbial ecology. Current limitations in this sphere of research are also addressed to frame a forward-looking perspective towards the realization of what we anticipate will become a pivotal toolkit for addressing environmental monitoring and management challenges in the years ahead.